PERILAKU LENTUR BALOK CASTELLATED MODIFIKASI DENGAN PENGAKU BAJA TULANGAN - , safitri syarif ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Castellated beam is a common term used for this type of open-web expanded beam. Open web is expanded girder beam and plate elements that have a body, then the bottom of the section is reversed and put back together between the top and bottom by means of shifted slightly then welded. The research objective of the thesis is behavior of flexural capacity of castellated beams with steel bars are connecting to compare the flexural capacity of the beams, to determine the pattern collapse of the beam, to determine the comparative value the deflection of each element that occurs in the beam and know the magnitude of stress and strain that occurs in castellated beams with steel reinforcement connector and compared with previous studies. The research was conducted by a research object 150x75x5x7 IWF profile is then cut into two parts with 3023 mm span length and the distance between the support is 2883 mm. The connection is made by adding reinforcing steel diameter of 22 mm were welded cross with 45o angle on each side of the IWF profile that has been cut and welded in the middle and added a cross reinforcement plates measuring 50x50x5 at the middle connecting reinforcement with an overall height of 275 mm along the test specimen. The amount of test specimens is 1 and as a support simple beam with static load testing method using two point loads within 771 mm. Observation are conducted bending behavior of the maximum load, strain, deflection that occurs due to the magnitude of the loading process and pattern collapse. The experimental results are compared with previous research connecting parts (Fatmawati, 2014), rectangular openings (Oliveira, 2012), hexagonal openings (Pribadi, 2012) and the SAP program in 2000 and Abaqus CAE version 6.7. The results of this eksperiment indicate that the modification of castellated beams have a maximum load of 106.4 kN with a deflection of 46.19 mm. Castellated beam pattern collapse in the form of local buckling modification. Castellated beam modification compared with previous research, the value of the maximum load modification castellated beams with steel reinforcement connector (106.4 kN) is higher than castellated beams hexagonal openings (54.9 kN), castellated beams with rectangular openings (24.6 kN) and junction modifications and castellated beams angled profile (36.4 kN). Keywords: castellated modification, bracing steel reinforcement, flexural behavior